Pattern of parasitic infections as public health problem among school children: A comparative study between rural and urban areas. Issue 1 (February 2016) - Alsubaie, Ali Saad R.; Azazy, Ahmed A.; Omer, Eltigani O.; Al-shibani, Latifa A.; Al-Mekhlafi, Abdulsalam Q.; Al-Khawlani, Faiz A.
الملخص: أهداف البحث: تهدف هذه الدراسة إلى تحديد مدى انتشار الإصابة بالطفيليات المعوية بين طلبة المدارس في أرياف ومدن منطقة "إب" في الجمهورية اليمنية. طرق البحث: تم اختيار المشاركين في هذه الدراسة المقطعية بشكل عشوائي من كل من المدن والأرياف. حللت ما مجموعه ٢٥٨ عينة براز من ١١٢ طفلا و ١٤٦ طفلة. استُخدِمت الطريقة المباشرة وطريقة التركيز في اختبار كل العينات لتحديد مراحل الطفيليات المعوية التي يمكن تشخيصها مجهريا. النتائج: من بين الـ ٢٥٨ عينة التي تمت دراستها تبين إصابة ١٤٨ طالبا بطفيلي واحد على الأقل٬ بانتشار إجمالي يقدر بـ ٥٧.٤٪. وتبينت الإصابة عند ٨٩ (٦٤.٥٪) من بين الـ ١٣٨ طفلا في المدن٬ بينما كانت الإصابة عند ٥٩ من بين الـ ١٢٠ طفلا (٤٩.٢٪) في المناطق الريفية. كما كانت الإصابة إحصائيا أعلى في المدن. وكانت أعلى نسبة إصابة بين الأطفال في سن ١٠-١١ سنة ٣١.٨٪ تلاها سن ١٢-١٣ سنة ٢٨.٤٪. وسُجلت نسب إصابة ٢٣.٦٪ و ١٦.٢٪ للفئة العمرية ٨-٩ سنوات و ١٤-١٥ سنة على التوالي. وكانت نسب توزيع الطفيليات المُكتشفة بين طلبة المدارس تنازليا على النحو التالي: إنتاميبا هستوليتيكا ٣٣.٧٪٬ وجيارديا لامبليا ٢٣.٦٪٬ وأسكارس لمبريكويديز ١٤.٣٪٬ وترايكيورس ترايكيورا ٩.٣٪٬ وهايمنولبس نانا ٦.٢٪٬ وشيستوسوما مانسوناي ٣.١٪٬ وأنكيلستوما دوودينالي ١.٢٪٬ وإنتروبيوس فيرمكيولارس ٠٬٨٪ وسترونقيلويديز ستيركورالس ٠٬٨٪. الاستنتاجات: بيَّنت الدراسة أن الإصابة بالطفيليات المعوية منتشرة بين أطفال المدارس وقد تكون مشكلة صحية عامة وخطيرة. تُبرز هذه الدراسة الحاجة إلى التدخلات الصحية العامة لمواجهة المشكلة. Abstract: Objective: This study aimed to determine the prevalence of intestinal parasitic infections among school children in rural and urban areas of the Ibb region in Yemen. Methods: In this cross-sectional study, participants were randomly recruited from both urban and rural areas. A total of 258 stool specimens from 112 boys and 146 girls were analysed. All samples were examined using both direct and concentration methods to identify microscopically possible diagnostic stages of intestinal parasites. Results: Of the 258 samples studied, 148 students were found to be positive for at least one parasite infection with an overall estimated prevalence of 57.4%. Of the 138 children from urban areas, 89 (64.5%) were found to be infected, whereas 59/120 (49.2%) students from rural areas were infected. The infection was statistically higher in urban areas ( X 2 = 6.164, P = 0.013). The infection rate was highest among the age group 10–11 years (31.8%) followed by 12–13 years (28.4%). Infection rates of 23.6% and 16.2% were recorded among 8- to 9-year-olds and 14- to 15-year-olds, respectively. The distributions of parasites among school children detected in descending order were: Entameba histolytica (33.7%), Giardia lamblia (23.6%), Ascaris lumbricoides (14.3%), Trichuris trichiura (9.3%), Hymenolepis nana (6.2%), Schistosoma mansoni (3.1%), Ancylostoma duodenale (1.2%), Enterobius vermicularis (0.8%) and Strongyloides stercoralis (0.8%). Conclusions: This study showed that infection by intestinal parasites is prevalent among school children and can be a crucial public health problem. This study emphasizes the need for public health interventions to tackle this problem.